Simultaneous observation of aerosols using the Durban and Reunion lidar systems - (:unkn) unknown (My University, 2012)
The observation of aerosols over Durban (29.9˚S, 31.0˚E, South Africa) and Reunion Island (20.8˚S, 55.5˚E) using Rayleigh-Mie lidar data collected during a coincident night of 21 May 2003 is presented in this paper. The temporal evolution of the Durban lidar backscatter signal for the corresponding night is used to study aerosols and clouds condition. The aerosol loading in the lower stratosphere is discussed in terms of aerosol extinction coefficient during this coincident night. A clear enhancement due to the presence of aerosols over Durban at the height level above 6 km is observed. The coincident profile of the aerosol extinction coefficient measured by the Durban and the Reunion lidar shows consistency during this day, with maximum observed at ~17 km for both lidars. However, the Reunion lidar shows higher aerosol extinction coefficient values.
Keywords: African Research